Quantitative determination of trace level (ng g−1) contents of rhodium and palladium in copper-rich minerals using LA-ICP-MS. Issue 3 (30th January 2020) - Yang, Zhaoping; Jackson, Simon E.; Cabri, Louis J.; Wee, Pamela; Longerich, Henry P.; Pawlak, Marcin
Abstract : Measurement of ng g −1 amounts of Rh and Pd in Cu-rich minerals by LA single quadrupole and tandem MS ICP-MS, using He collision gas and (NH3 )/He (10%/90%) reaction gas, respectively, to attenuate CuAr interferences on 103 Rh and 105 Pd. Abstract : This study reports on the efficacy of measuring low ng g −1 contents of Rh and Pd in Cu-rich minerals by laser ablation single quadrupole (Agilent 7700x) and tandem MS (Agilent 8900x) ICP-MS, using helium (He) collision gas and a mixture of ammonia (NH3 )/He (10%/90%) reaction gas, respectively, to attenuate CuAr interferences on 103 Rh and 105 Pd. Results are compared with values obtained from digested separates of the same minerals (three synthetic Cu-rich Fe sulphides, seven samples of chalcopyrite (CuFeS2 ) and two of bornite (Cu5 FeS4 ) containing 24.17% to 63.31% Cu, less than 10 ng g −1 Rh and less than 250 ng g −1 Pd) analyzed using an Agilent 8800x ICP-MS/MS in NH3 /He reaction mode. Using the LA-ICP-MS/MS at an optimized NH3 /He flow rate (0.3 mL min −1 ), the CuAr contributions to 103 Rh and 105 Pd were less than 2.3 ng g −1, which was a reduction of more than two orders of magnitude compared to those obtained using the single quadrupole LA-ICP-MS at an optimized He collision gas flow (5 mL min −1 ). The method limits of detection (MLOD) for 103 Rh (1.7 ng g −1 ) and 105 Pd (7.0 ng g −1 ) obtained using LA-ICP-MS/MS at the optimized NH3 /He flow rate with a 110 μm ablation spot size were approximately an order of magnitude lower than those (16 ng g −1 for Rh and 48 ng g −1 for Pd) obtained using single quadrupole LA-ICP-MS at the optimized He collision gas flow rate. The accuracy (difference from values for digested separates) and precision (1RSD) of ng g −1 -level LA-ICP-MS/MS measurements of Rh and Pd ( 105 Pd) in Cu-rich minerals were in the range of 0.5% to 19% and 19% to 31%, respectively. Moreover, this study shows that neither a linear CuAr interference correction strategy nor the interference correction procedure of P. J. Sylvester, Mineral. Assoc. Can., Short Course Ser., 2001, vol. 29, p. 203 works effectively for accurate and precise LA-ICP-MS measurement of low ng g −1 contents of Rh and Pd in Cu-rich minerals. The most accurate and precise measurement of Rh at less than 10 ng g −1 and Pd at ca. 100 ng g −1 in Cu-rich minerals is achieved using the Agilent 8900x LA-ICP-MS/MS in MS/MS acquisition mode at an optimized NH3 /He reaction gas flow rate without a CuAr interference correction. These results demonstrate the potential for LA-ICP-MS/MS to be widely used for the quantitative determination of trace level contents of the light PGE in transition metal sulphide minerals.